2019
DOI: 10.1177/2150135119872196
|View full text |Cite
|
Sign up to set email alerts
|

Budesonide for Protein Losing Enteropathy in Patients with Fontan Circulation: A Systematic Review and Meta-Analysis

Abstract: Background: Recent studies have shown that oral budesonide can be used to improve albumin level in patients with protein-losing enteropathy (PLE) following Fontan procedure. However, there has never been a systematic review and meta-analysis to confirm this finding. We performed a systematic review and meta-analysis to explore the therapeutic effect of budesonide in patients with PLE post-Fontan procedure. Methods: We searched the databases of MEDLINE and EMBASE from inception to January 2019. Included studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…A recent meta-analysis showed that it is effective in ameliorating serum albumin levels in this setting. 9 Long-term complications of GD which were not observed before the availability of ERT are becoming more apparent with increased life expectancy due to ERT. All five reported GD cases with PLE belong to post-ERT era.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis showed that it is effective in ameliorating serum albumin levels in this setting. 9 Long-term complications of GD which were not observed before the availability of ERT are becoming more apparent with increased life expectancy due to ERT. All five reported GD cases with PLE belong to post-ERT era.…”
Section: Discussionmentioning
confidence: 99%
“…Because long-term systemic steroid administration may lead to side effects such as osteo- who have undergone the Fontan procedure for congenital heart disease. 13,14 Inhaled budesonide-formoterol is a combination of a corticosteroid and long-acting beta2-adrenergic agonist. No reports have shown the efficacy and long-term improvements induced by inhaled budesonide-formoterol treatment.…”
Section: E T T E R T O T H E E D I T O R Regression Of Kaposiform Lym...mentioning
confidence: 99%
“…It is hypothesized that midodrine works by its effect on tone in the smooth muscle cells in the lymphatic vessels, though additional work is needed to confirm this hypothesis ( 113 , 114 ). Additional medical treatments for patients with PLE include oral budesonide and octreotide, but use may not reduce the need for transplant over the long term ( 65 , 115 , 116 ).…”
Section: Treatmentmentioning
confidence: 99%